Adaptive laboratory evolution of Klebsiella pneumoniae for improving 2, 3-butanediol production. Issue 6 (1st November 2016) - Li, Hongbiao; Zhang, Genlin; Dang, Yanyan
ABSTRACT: Microbial production of 2, 3-butanediol is limited by the toxic components in the lignocellulose hydrolysate. To improve the 2, 3-butanediol production via Klebsiella pneumoniae from cotton stalk hydrolysate, a method coupling a high tolerance of strain and detoxification of the hydrolysate was thus investigated in this study. The strain tolerance of K. pneumoniae to the cotton stalk hydrolysate was improved via an adaptive laboratory evolution, which involved a stepwise increase in the hydrolysate concentration in the medium. Compared with the initial strain, the resulting strain increased the biomass 3.2-fold in a medium of 20 g/L hydrolysate and produced 10.45 g/L of 2, 3-butanediol at an optimal concentration of 60 g/L hydrolysate. After detoxification of cotton stalk hydrolysate, the cell metabolism of K. pneumoniae was further promoted, and the 2, 3-butanediol production increased by 1.2 folds. Using fed-batch fermentation, the concentration of 2, 3-butanediol reached 35.5 g/L with a yield of 0.43 g/g. The results demonstrated that the bioconversion of low-cost cotton stalk hydrolysate into 2, 3-butanediol improves the economics of microbial 2, 3-butanediol production.